IPhone for Dummies : A Wiley Brand - Baig, Edward C. and LeVitus, Bob (Chichester For Dummies, 2014)
The perennial bestseller on having fun with your iPhone Finding it hard to put your iPhone down, but still haven't figured out how to make the most of its capabilities? Packed with fun instructions, tips, and advice, iPhone For Dummies makes it easy to navigate your way around your new device and unlock all of its state-of-the-art features. The book walks you through surfing the web, staying connected with Facebook and FaceTime, sharing photos and videos, rocking out with music, and much more. Inside, veteran Dummies authors and Mac gurus Edward C. Baig and Bob ""Dr. Mac"" LeVitus share their.
include Illustrations, Tables and Index
Keywords: iPhone (Smartphone)